2011
DOI: 10.1002/mrm.22799
|View full text |Cite
|
Sign up to set email alerts
|

MRI with zero echo time: Hard versus sweep pulse excitation

Abstract: Zero echo time can be obtained in MRI by performing radiofrequency (RF) excitation as well as acquisition in the presence of a constant gradient applied for purely frequencyencoded, radial centre-out k-space encoding. In this approach, the spatially nonselective excitation must uniformly cover the full frequency bandwidth spanned by the readout gradient. This can be accomplished either by short, hard RF pulses or by pulses with a frequency sweep as used in the SWIFT (Sweep imaging with Fourier transform) metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
156
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(158 citation statements)
references
References 18 publications
1
156
0
1
Order By: Relevance
“…A UTE sequence provides the possibility to obtain MR images at echo time below 1 ms, 12 but this sequence has some intrinsic problems, like errors from eddy-currents generated by the gradient ramps, which need to be corrected by k-space trajectory measurements; additionally, the ramp reduces the signal to noise ratio. 21 Therefore, the use of ZTE imaging, which samples signal without an echo time delay, was explored to visualize bone and CPC at optimal signal strength. In this study, it was shown that with ZTE indeed good images of bone and CPC could be obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A UTE sequence provides the possibility to obtain MR images at echo time below 1 ms, 12 but this sequence has some intrinsic problems, like errors from eddy-currents generated by the gradient ramps, which need to be corrected by k-space trajectory measurements; additionally, the ramp reduces the signal to noise ratio. 21 Therefore, the use of ZTE imaging, which samples signal without an echo time delay, was explored to visualize bone and CPC at optimal signal strength. In this study, it was shown that with ZTE indeed good images of bone and CPC could be obtained.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Another approach without echo time spin evolution is zero echo time (ZTE) MR. [17][18][19][20] It is closely related to UTE and has been implemented on small animal MR systems. 21 A hard RF pulse is applied to accomplish spatially nonselective excitation that covers the full frequency bandwidth spanned by the readout gradient. Excitation and acquisition is both in the presence of a constant gradient purely used for frequency encoding by 3D radial center-out k-space trajectories.…”
Section: Introductionmentioning
confidence: 99%
“…MRI is the gold standard for soft tissue imaging, such as breast and prostate, but has recently started to be exploited for hard tissue applications too. The development of short Echo Time acquisition sequences, like Ultra Short Echo Time and ZTE, [8][9][10]34 opened the way to new possibilities for bone-related applications.…”
Section: Dual Contrast Agent For Bone Imagingmentioning
confidence: 99%
“…On the other hand, recent developments in the field of magnetic resonance imaging (MRI) open the way to a completely new scenario of high-resolution bone visualization applications. [6][7][8] A common problem of all imaging modalities remains the high similarity between CPCs and the mineral phase of the bone, which makes it difficult, if not impossible, to clearly discriminate the materials. 9 Several opacifiers have already been proposed to enhance the contrast of CPCs for CT (i.e., barium sulfate, tantalum oxide) and MRI (Iron Oxide Particles, gadolinium).…”
Section: Introductionmentioning
confidence: 99%
“…first accumulate in the lungs which has a low water content (and thus low 1 H signal) and is difficult to image with MR due to susceptibility related signal loss via multiple air-tissue interfaces. Improved imaging protocols that use pulse sequences with shorter echo times, [60][61][62][63] or surface coils that provide high sensitivity in a localized region may improve sensitivity in the lungs to allow imaging of 19 /SzJ (NSG) mice were purchased from The Jackson Laboratory (Bar Harbor, Maine) and used between 8-16 weeks of age. All animals were bred and housed in a pathogen-free facility throughout the study.…”
mentioning
confidence: 99%